2014
DOI: 10.1021/nn5046486
|View full text |Cite
|
Sign up to set email alerts
|

Convex Nanobending at a Moving Contact Line: The Missing Mesoscopic Link in Dynamic Wetting

Abstract: The morphological information on the very front of a spreading liquid is fundamental to our understanding of dynamic wetting. Debate has lasted for years concerning the nanoscopic local angles and the transition from them to the macroscopic counterpart, θ(D). This study of nonvolatile liquids analyzes the interface profile near the advancing contact line using an advanced atomic force microscopy. The interface is found following the macroscopic profile until bending in a convex profile around 20 nm from the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 44 publications
6
46
1
Order By: Relevance
“…That is, a liquid flow is simulated in steady conditions in a macroscopic droplet forced to move in between two solid substrates separated by the distance H M = 13.7 L s using the macroscopic set of parameters α 1 = 1.6 and α 2 = 0.51 directly calculated from the set of interfacial parameters h The results of continuum simulations are also in a very good quantitative agreement with the MDS results. Consider, for example, distributions of tangential u z and normal u n velocities at the solid substrate, Figure 6 47 The characteristic value of the pressure at the contact line obtained in the FEM simulations is consistent with the viscous stresses, which are expected to be developed on the length scale of one slip length L s , that is p ≈ µU/L s . Note, that the pressure regularity also suggests, that in our case there are no spurious solutions reported in reference.…”
Section: Resultssupporting
confidence: 58%
“…That is, a liquid flow is simulated in steady conditions in a macroscopic droplet forced to move in between two solid substrates separated by the distance H M = 13.7 L s using the macroscopic set of parameters α 1 = 1.6 and α 2 = 0.51 directly calculated from the set of interfacial parameters h The results of continuum simulations are also in a very good quantitative agreement with the MDS results. Consider, for example, distributions of tangential u z and normal u n velocities at the solid substrate, Figure 6 47 The characteristic value of the pressure at the contact line obtained in the FEM simulations is consistent with the viscous stresses, which are expected to be developed on the length scale of one slip length L s , that is p ≈ µU/L s . Note, that the pressure regularity also suggests, that in our case there are no spurious solutions reported in reference.…”
Section: Resultssupporting
confidence: 58%
“…Spreading of droplets in the partial-wetting regime can therefore serve as an alternative test for the height-dependence of surface tension; we have shown that our new model allows investigations of the spreading process without the need for precursor films (Pahlavan et al 2015). Visualization of the contactline motion at micro/nano-scales (Chen et al 2014;Qian et al 2015;McGraw et al 2016;Deng et al 2016) could therefore lead the way in refining and validating models for interfacial flows.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Above the depletion region, wave-like spatial undulations of liquid density have been reported, [17][18][19] implying a new mechanism of energy dissipation in the form of layer-by-layer friction during the process of dynamic wetting. [20][21][22] It was also reported that such spatial undulations can break the ideal tetrahedron geometry of hydrogen bonds, 23 which is usually formed in bulk water, and may give rise to the polarity of interfacial water. 24,25 In this respect, the identication of truly interfacial molecules (ITIM) analyses revealed that the effect of structural change on interfacial properties may be limited to the close vicinity of the interface, i.e., the rst molecular layer.…”
Section: Introductionmentioning
confidence: 99%